Embodied Political Influencers: How U.S. Anti-Abortion Actors Co-Opt Narratives of Marginalization - Zelly Martin; Gabrielle D. Beacken; Inga K. Trauthig; Samuel C. Woolley (Social Media + Society)
U.S. anti-abortion activists use social media to advocate for their cause. While influencer scholarship has proliferated within media studies, the advent of political influencers remains understudied, despite their ability to influence public opinion. Through 16 interviews with anti-abortion political influencers combined with digital observation, we examine the emergent tactics of “progressive” anti-abortion influencers. We find that these influencers co-opt marginalized communities’ ideological frameworks and experiences of discrimination in an effort to influence public opinion on abortion. We build upon the concept of identity propaganda from Reddi, Kuo, and Kreiss, but crucially reveal the ways in which these influencers mobilize their own experiences of oppression as members of marginalized communities themselves. Thus, we put forth the theoretical concept of embodied political influencers to articulate these influencers’ aim to change political opinion through identifying as members of marginalized groups, calling on their own historical—and at times contemporary—experiences of subjugation to propagate embodied propaganda.